The formation of benzoxacin-3-ones via intramolecular Nicholas reactions and synthesis of 8-membered heliannuols. Issue 33 (10th August 2021) - St. Onge, Brent; Green, James R.
Abstract : Intramolecular Nicholas reactions have been shown to give dehydrobenzoxacin-3-one-Co2 (CO)6 complexes. This allows the synthesis of (±)-heliannuol K methyl ether and the formal syntheses of (±)-heliannuol K, (±)-heliannuol A, and (−)-heliannuol L. Abstract : The γ-carbonyl cations generated from propargyl ether-Co2 (CO)6 complexes undergo intramolecular Nicholas reactions to give dehydrobenzoxacin-3-one-Co2 (CO)6 complexes in good yields. Reductive decomplexation and subsequent manipulation allows the synthesis of (±)-heliannuol K methyl ether and the formal syntheses of (±)-heliannuol K, (±)-heliannuol A, and (−)-heliannuol L.